Insulin-like growth factor ligands, receptors, and binding proteins in cancer. - Foulstone, E; Prince, S; Zaccheo, O; Burns, J; Harper, J; Jacobs, C; Church, D; Hassan, A (2005)
This review aims to summarize experimental evidence supporting the role of the insulin-like growth factor (IGF) signalling system in the progression, maintenance, and treatment of cancer. These data implicate the IGF system as an important modifier of cancer cell proliferation, survival, growth, and treatment sensitivity. The role of the IGF system in cancer should be examined in the context of the extra-cellular and intra-cellular signalling networks, in particular: phosphatidylinositol 3-kinase (PI3K), protein kinase B (Akt/PKB), mammalian target of rapamycin (mTOR), and forkhead transcription factors (FOXO). This review highlights evidence derived from molecular structure and functional genetics with respect to how the extra-cellular components of the IGF system function normally, and their subsequent modifications in cancer. The therapeutic relevance of the research evidence described is also addressed, as the challenge is to apply this knowledge to human health.